The Role Of Community Health Workers in Enhancing Healthcare Access For Vulnerable Populations - Anna Kowalska; Marcin Nowak; Katarzyna Zielinska (International Journal of Health and Medicine, 2024)
This study explores the impact of community health workers (CHWs) on improving healthcare access for vulnerable populations. By examining programs in urban and rural settings, the research highlights how CHWs facilitate education, outreach, and navigation of healthcare services. The findings indicate that CHWs play a vital role in bridging gaps in healthcare access, ultimately leading to better health outcomes for underserved communities.